A Validated Set of Fluorescent-Protein-Based Markers for Major Organelles in Yeast (Saccharomyces cerevisiae) - Jing Zhu (American Society for Microbiology, 2019)
ABSTRACT Eukaryotic cells share a basic scheme of internal organization featuring membrane-based organelles. The use of fluorescent proteins (FPs) greatly facilitated live-cell imaging of organelle dynamics and protein trafficking. One major limitation of this approach is that the fusion of an FP to a target protein can and often does compromise the function of the target protein and alter its subcellular localization. The optimization process to obtain a desirable fusion construct can be time-consuming or even unsuccessful. In this work, we set out to provide a validated set of FP-based markers for major organelles in the budding yeast (Saccharomyces cerevisiae). Out of over 160 plasmids constructed, we present a final set of 42 plasmids, the recommendations for which are backed up by meticulous evaluations. The tool set includes three colors (green, red, and blue) and covers the endoplasmic reticulum (ER), nucleus, Golgi apparatus, endosomes, vacuoles, mitochondria, peroxisomes, and lipid droplets. The fidelity of the markers was established by systematic cross-comparison and quantification. Functional assays were performed to examine the impact of marker expression on the secretory pathway, endocytic pathway, and metabolic activities of mitochondria and peroxisomes. Concomitantly, our work constitutes a reassessment of organelle identities in this model organism. Our data support the recognition that “late Golgi” and “early endosomes,” two seemingly distinct terms, denote the same compartment in yeast. Conversely, all other organelles can be visually separated from each other at the resolution of conventional light microscopy, and quantification results justify their classification as distinct entities. IMPORTANCE Cells contain elaborate internal structures. For eukaryotic cells, like those in our bodies, the internal space is compartmentalized into membrane-bound organelles, each tasked with specialized functions. Oftentimes, one needs to visualize organelles to understand a complex cellular process. Here, we provide a validated set of fluorescent protein-based markers for major organelles in budding yeast. Yeast is a commonly used model when investigating basic mechanisms shared among eukaryotes. Fluorescent proteins are produced by cells themselves, avoiding the need for expensive chemical dyes. Through extensive cross-comparison, we make sure that each of our markers labels and only labels the intended organelle. We also carefully examined if the presence of our markers has any negative impact on the functionality of the cells and found none. Our work also helps answer a related question: are the structures we see really what we think they are?